[(18)F]- and [(11)C]-Labeled N-benzyl-isatin sulfonamide analogues as PET tracers for apoptosis: synthesis, radiolabeling mechanism, and in vivo imaging of apoptosis in Fas-treated mice - Zhou, Dong (2009)
The radiolabeled isatin sulfonamide caspase-3 inhibitor, [(18)F]2 (WC-II-89), is a potential PET radiotracer for noninvasive imaging of apoptosis. The radiolabeling mechanism was studied by (13)C NMR, ESI/MS, and computational calculations. It was found that the high electrophilicity of the C3 carbonyl group in the isatin ring, which served as a trap for [(18)F]fluoride, was responsible for the failure of the radiolabeling via nucleophilic substitution of the mesylate group in 7a by [(18)F]fluoride. Once treated with a strong base, 7a opened the isatin ring completely to form an isatinate intermediate 16, which lost the ability to trap [(18)F]fluoride, thereby allowing the displacement of the mesylate group to afford the (18)F-labeled isatinate 17. [(18)F]17 can be converted to isatin [(18)F]2 efficiently under acidic conditions. The ring-opening and re-closure of the isatin ring under basic and acidic conditions were confirmed by reversed phase HPLC analysis, ESI/MS and (13)C NMR studies. Computational studies of model compounds also support the above proposed mechanism. Similarly, the ring-opening and re-closure method was used successfully in the synthesis of the (11)C labeled isatin sulfonamide analogue [(11)C]4 (WC-98). A microPET imaging study using [(11)C]4 in the Fas liver apoptosis model demonstrated retained activity in the target organ (liver) of the treated mice. Increased caspase-3 activation in the liver was verified by the fluorometric caspase-3 enzyme assay. Therefore, this study provides a useful method for radio-synthesis of isatin derivative radiotracers for PET and SPECT studies, and [(11)C]4 is a potential PET radiotracer for noninvasive imaging of apoptosis.